Effect of Electroacupuncture on Chondrocyte Apoptosis in Knee Osteoarthritis Rat Based on PI3K/Akt Signaling Pathway - Yuanyuan ZHANG; Xinyu JIANG; Xihai LI; Mingxia WU (康复学报)
Objective:To investigate the effect of electroacupuncture on chondrocyte apoptosis in knee osteoarthritis (KOA) rat based on PI3K/Akt signaling pathway.Methods:A total of 50 male Sprague Dawley (SD) rats, aged eight weeks, weighing (200±20) g were selected and randomly divided into sham operation group, model group, experiment group 1, experiment group 2 and experiment group 3. After two weeks of adaptive feeding, the sham operation group received incision in the medial aspect of the joint, the muscles and ligaments were separated layer by layer, the joint cavity was exposed and then suturing. Rat models were replicated in the other four groups by the method of modified Hulth. The sham operation group and the model group did not receive electroacupuncture intervention. In the experimental group 1, the bilateral internal and external knee eyes of rats were directly punctured 3-5 mm, once a day, 15 minutes each time. In the experimental group 2, the bilateral internal and external knee eyes of rats were directly punctured 3-5 mm, once a day, 30 minutes each time. In the experimental group 3, points (non-meridian and non-acupoint) of rats were obliquely pricked upward for 3-5 mm, once a day, 15 minutes each time. The three experimental groups received electroacupuncture for 12 weeks, 5 times a week. Electroacupuncture parameters: dilatational wave, frequency of sparse wave 2 Hz and dense wave 10 Hz, pulse width less than 1 ms, output voltage less than 10 V, and the extent was that the local muscles began to shake slightly and the rats did not struggle. After 12 weeks of electroacupuncture intervention, the articular cartilage and synovium were harvested, and the changes of histomorphology of articular cartilage were observed under light microscope by hematoxylin-eosin staining and toluidine blue staining. The degree of cartilage degeneration was evaluated by modified Mankin's scoring standard. The contents of interleukin-1β(IL-1β) and tumor necrosis factor-α(TNF-α) in synovium were detected by immunosorbent assay (ELISA). The expression of PI3K, Akt, Bcl-2, Bax mRNA and protein were detected by real-time quantitative PCR and Western blot.Results:Compared with the sham operation group, the cartilage morphology of the model group was disordered, the number of chondrocytes was significantly reduced, the matrix staining was lost, the tidal line was distorted and incomplete, Mankin's score was significantly increased (P< 0.01), the expressions of IL-1β and TNF-α in the synovium were significantly increased (P< 0.01), the expressions of PI3K, Akt and Bcl-2 mRNA and protein were significantly decreased (P< 0.01), and the expression of Bax mRNA and protein were significantly increased (P< 0.01). Compared with the model group, the cartilage morphology of the experimental group 1 and the experimental group 2 was neat, the number of chondrocytes was increased, the matrix staining was deepened, the tidal line was complete, Mankin's score was significantly decreased (P< 0.01), the expressions of IL-1β and TNF-α in the synovium were significantly decreased (P< 0.01), the expressions of PI3K, Akt and Bcl-2 mRNA and protein were significantly increased (P< 0.01), and the expression of Bax mRNA and protein were significantly decreased (P< 0.01). The morphological structure of the experimental group 3 was not improved, and there was no significant difference in the results of the indicators (P> 0.05).Conclusion:Electroacupuncture of the bilateral internal and external knee eyes can improve the expression of Bcl-2, decrease the expression of Bax, and reduce the production of inflammatory factors IL-1β and TNF-α by regulating PI3K/Akt signaling pathway, thereby inhibiting the degradation of cartilage matrix and apoptosis of chondrocytes, protecting and improving the morphology of cartilage, and delaying the development of knee osteoarthritis.